Characteristics and disinfection by-product formation potential of dissolved organic matter in reservoir water in cold area. (August 2022) - Xu, Xiaotong; Wang, Binyuan; Shen, Jimin; Kang, Jing; Zhao, Shengxin; Yan, Pengwei; Chen, Zhonglin
Abstract: The severe cold in winter with harsh natural conditions in Northeastern China seriously affect the water quality of the reservoir, showing the increased content and more complex types of organic matter, which brings severe challenges to the control of disinfection by-products (DBPs) in drinking water treatment with reservoir water as the water source. In this study, the fractions of dissolved organic matter (DOM) in source water at before ice formation period (P1), ice-age period (P2), and ice begin to melt period (P3) were separated by membrane separation technology. Subsequently, the contributions of DOM fractions with different molecular weights (MW) to DOC, UV254, and SUVA254, and their disinfection by-product formation potential (DBPFP) were evaluated. Although DOM with high MW (5–10 kDa) contributed the most to dissolved organic carbon (DOC) and UV254, but the contribution of DOM with low MW (0–1 kDa) to DBPs formation could not be ignored, especially during ice-age period. There was no significant difference in the total numbers of DOM formula belonged to low MW fraction at these three periods, mainly including lignin, followed by N-containing saturated compounds and tannins. Additionally, redundancy analysis revealed that DOC and UV254 as the predictors had good correlation with DBPFP, while SUVA254 could not be used as a single indicator to predict the generation potential of DBPs, and could be used as the prediction factors together with AImodwa parameter closely related to DBPFP. The study provided key information for controlling the DBPs formation of DOM in water, especially in the ice-age period, and provided the theoretical basis for water plant production. Graphical abstract: Image 1 Highlights: DOM in reservoir water had high content and complex structure during ice-covered period. The fraction with 5 kDa＜MW＜10 kDa accounted for the largest proportion of DOM. The fraction with 5 kDa＜MW＜10 kDa and MW＜1 kDa were the main precursor of THMFP and CHFP. Oxygen-containing functional groups had greater influence on CHFP. The low MW DOM (0–1 kDa) was mainly distributed in the higher MW of 0.5–1 kDa.